Diminished Anticipatory and Consummatory Pleasure in Dysphoria: Evidence From an Experience Sampling Study - Li, Xu; Zhang, Yu-Ting; Huang, Zhi-Jing; Chen, Xue-Lei; Yuan, Feng-Hui; Sun, Xiao-Jun (Frontiers in Psychology, 2019)
Anhedonia, the experience of diminished pleasure, is a core feature of major depressive disorder (MDD) and is often present long before the diagnosis of depression. Most previous studies have investigated anhedonia with self-report measures of trait anhedonia or with behavioral paradigms using laboratory stimuli, and the real-time characteristics of hedonic processing in subclinical depression remain under-investigated. We used the experience sampling method to evaluate momentary experience of hedonic feelings in the context of daily life. Dysphoric (n = 49) and non-dysphoric (n = 51) college students completed assessments of their current positive affect (PA), as well as state anticipatory and consummatory pleasure, 3 or 4 times a day every day for two weeks. The results showed that dysphoric individuals reported less state anticipatory and consummatory pleasure compared with non-dysphoric individuals. Moreover, significant time-lagged associations between anticipatory pleasure and follow-up consummatory pleasure were found in the whole sample, after adjustment for current PA. The current findings thus hold considerable promise in advancing our understanding of anhedonia as well as the important role of state anticipatory pleasure in relation to depression.